Private Life in New Kingdom Egypt - Meskell, Lynn (Princeton University Press, 2018)
Much of the literature on ancient Egypt centers on pharaohs or on elite conceptions of the afterlife. This scintillating book examines how ordinary ancient Egyptians lived their lives. Drawing on the remarkably rich and detailed archaeological, iconographic, and textual evidence from some 450 years of the New Kingdom, as well as recent theoretical innovations from several fields, it reconstructs private and social life from birth to death. The result is a meaningful portrait composed of individual biographies, communities, and landscapes. Structured according to the cycles of life, the book relies on categories that the ancient Egyptians themselves used to make sense of their lives. Lynn Meskell gracefully sifts the evidence to reveal Egyptian domestic arrangements, social and family dynamics, sexuality, emotional experience, and attitudes toward the cadences of human life. She discusses how the Egyptians of the New Kingdom constituted and experienced self, kinship, life stages, reproduction, and social organization. And she examines their creation of communities and the material conditions in which they lived. Also included is neglected information on the formation of locality and the construction of gender and sexual identity and new evidence from the mortuary record, including important new data on the burial of children. Throughout, Meskell is careful to highlight differences among ancient Egyptians--the ways, for instance, that ethnicity, marital status, age, gender, and occupation patterned their experiences. Readers will come away from this book with new insights on how life may have been experienced and conceived of by ancient Egyptians in all their variety. This makes Private Life in New Kingdom Egypt unique in Egyptology and fascinating to read